HUBUNGAN KONDISI PSIKOSOSIAL LANSIA HIPERTENSI DENGAN KEJADIAN INSOMNIA - Agustono Agustono; Reni Zulfitri; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Psychosocial condition in elderly hypertension can cause some health problems, one of that is insomnia. This study aimed to know the correlation between psychosocial status in elderly hypertension and insomnia cases in public health center area in Puskesmas Payung Sekaki, Pekanbaru city. The design of this research was descriptive correlation using cross sectional approach. The sample of this research were 85 persons with using purposive sampling technique. The data was collected by using valid and reliable questionnaire. The study analysis was univariate and bivariate using chisquare test. The research result showed that the majority of research subject 60-74 years old were 65 respondents (76,5%), 47 respondents (55,3%) were women , 82 respondents (96,5%) were moslems, 41 respondents (48,2%) were minangness, 47 respondents (55,3%) were elementary background, 48 respondents (56,5%) were already marriage, while 71 respondents (83,5%) were not answer. Based on the time of getting hypertension that were at >3-5 years consist of 36 respondents (42,4%), the research result showed that commonly respondents of hypertension having healthy psychosocial condition as much as 48 respondents (56,5%) and commonly elderly getting insomnia was 66 respondents (77,6%). Chi-square test showed that p value (0,012) < α (0,05), so it can be concluded that has significant correlation between psychosocial status in elderly hypertension and insomnia cases. Elderly can increase their quality of life and avoid psychosocial problem to prevent health problem like insomnia. Keywords: elderly, hypertension, insomnia cases, psychosocial condition